Typology of environment-related provisions in regional trade agreements - José-Antonio Monteiro (World Trade Organization (WTO), 2016)
The last 25 years have witnessed a rapid increase in regional trade agreements (RTAs). Although RTAs generally aim at lowering tariff and non-tariff trade barriers, an increasing number of trade agreements extend their scope to cover specific policy areas such as environmental protection and sustainable development. This paper establishes a comprehensive typology and quantitative analysis of environment-related provisions included in RTAs. The analysis covers all the RTAs currently into force that have been notified to the WTO between 1957 and May 2016, namely 270 trade agreements. While environmental exceptions, along with environmental cooperation continue to be the most common types of environment-related provisions, many other different types of provisions are incorporated in an increasing number of RTAs. The common feature of all environment-related provisions, including environmental exceptions, is their heterogeneity in terms of structure, language and scope.
Keywords: F13; F18; 330; Regional Trade Agreements; Environment; Sustainable Development